Genetic correlation and path analysis of agronomical traits of soybean (Glycine max) lines infected by CpMMV (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Faot MM, Zubaidah S, Kuswantoro H. 2019. Genetic correlation and path analysis of agronomical traits of soybean (Glycine max) lines infected by CpMMV. Biodiversitas 20: 1496-1503. CpMMV is a virus that can decrease soybean production. The virus vector is an insect where the control is carried out using a chemical insecticide that is less environmentally friendly. Developing a superior variety of soybean that is resistant to CpMMV is one of the solutions to solve such a problem. This research aimed to study the relationship of agronomical traits to the yield of soybean line infected by CpMMV. Ten lines and two varieties of soybean with four replications was used in this study in a randomized complete block design. Bemisia tabaci was used in CpMMV infestation as the vector of the disease. Rearing Bemisia tabaci was done forty days before sowing the main experiment, and it placed surrounding the main experiment plots. The observation variables were disease severity, days to flowering and maturity, plant height, length, width and ratio of the leaf, number of branches and reproductive nodes, number of filled and unfilled pods, number of seeds, 100 seeds weight, and seed yield per plant. The data was analyzed for genotypic and phenotypic correlation, and the path analysis for direct and indirect effects of disease severity, and agronomical characters. The results showed that CpMMV infestation caused disease severity by about 20-28.5%. A significant positive phenotypic correlation to the seed yield per plant was shown by the number of reproductive nodes and the 100 seeds weight. Meanwhile, a significant positive genotypic correlation to the seed yield per plant was shown by the days to maturity and the number of branches. The number of reproductive nodes, the 100 seeds weight, and the number of seeds per plant showed a high direct effect to the seed yield per plant. The high positive indirect effect was also shown by the number of filled pods, days to flowering, plant height, leaf length, leaf width, the number of reproductive nodes, and the number of branches through the number of seeds per plant was also. Therefore, the selection criteria for high yielding CpMMV-resistant soybean lines can be based on the number of reproductive nodes and 100 seeds weight.
Keywords: CpMMV, genetic correlation, path analysis